Genetic variation of 3β-hydroxysteroid dehydrogenase type II in three racial/ethnic groups: Implications for prostate cancer risk - Devgan, S.A. (2016)
10.1002/(SICI)1097-0045(19970915)33:1<9::AID-PROS2>3.0.CO;2-H